Picosecond-controlled switching of high-voltage gas discharge; Technical Physics Letters; Vol. 34, № 10 - Mesyats G. A. Gennady Andreyevich; Sharypov K. A.; Shpak V. G.; Shunailov S. A.; Yalandin M. I. (2008, 2008)
В фонде НТБ ТПУ отсутствует